PERAN MATA KULIAH AL-ISLAM KEMUHAMMADIYAHAN DALAM MENANAMKAN MOTIVASI DAN POLA BERFIKIR UNTUK MEMBENTUK AHLAK AL-KARIMAH PADA UNIVERSITAS MUHAMMADIYAH SIDENRENG RAPPANG - Hijaz Tahir Hijaz Tahir (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This research was conducted aiming to determine the role of the Al-Islam Kemuhammadiyahan course in the formation of student character which is expected to provide significant enlightenment and understanding that ahlakul karima is actually a mandate from Allah swt, which is guided for all humans. Nowadays, it seems as if there is a shift in values ​​where etiquette and politeness seem to have almost faded away from the identity of most of the younger generation, while this mazmumah's moral attitude seems to be increasingly fertile in daily behavior. so that it is an obligation for every lecturer in AIK courses to shape the character of students who have an Islamic feel at the Muhammadiyah University of Sidrap. This study uses a qualitative descriptive analysis approach. The results of the study were carried out by internalizing the values ​​of morality, aqidah (according to the Qur'an and As-Sunnah). In this research, the approach taken is through a qualitative approach. The use of a qualitative approach in this research is to match the empirical reality with the applicable theory by using a descriptive method. Qualitative research is research in which researchers in carrying out their activities use observation techniques, interviews or interviews, content analysis, and perform other data collection methods to present responses as subject behavior.